Menyikapi Rahasia di Balik Rasio dan Rasa pada Manusia - Aloi Kamarasyid (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
The sciense of human will not able to solve all of things, according to the words of Allah: “And we are not given a science except a little”, (Q.S 17/ Al-Isra’: 85). Instinct of human must get a direction of Allah who is explained at his book. Unless the instinct will be wrong in its channel. The position of instinct and intelligence at Islam ethics, both are necessary to be used and dropped well by counselling and directing which are settled in Al-Qur’an and the guide of propnet Muhammad SAW. Philosophy of Islam also bases on or follows the healthy intelligence to interpret all of problems of divinity, human and nature, because of necessity of thing is intelligence. It is either a subject or object of thinking. From it exits an active intelligence, because it is the first which is created by Allah. By intelligence we analyze and prove about truthm, to expose the scientific realities, about filling, idealism, ethics, law, aesthetics, extra sensory perception, and purity of heart. Intelligence is a door of science. There are not all of sciences are revealed but there are obliged to be deductive by intelligence through experiment. Allah also gives Islam Religion which is an association of power of God which is given to human (command and prohibition). Islam Religion is a mercy to manage intelligence, feeling, heart and emotion of human. We are obliged to believe, to study so that we know which is comman ded and prohibited, to do and to broadcast the Islam Religion well and truly according to his instruction (Muslim Law).